The Health‐Related Quality of Life for Cemented Versus Uncemented Hemiarthroplasty in Elderly Patients With Femoral Neck Fractures: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials - Mohanad Samaheen; Maen Mohammad; Mikhail Salzmann; Nikolai Ramadanov (Orthopaedic Surgery)
ABSTRACT Objective Femoral neck fractures in the elderly are a global health issue, with the choice between cemented and uncemented hemiarthroplasty remaining a topic of debate. This systematic review and meta‐analysis aims to compare the effects of the two surgical options on health‐related quality of life (HRQoL), mortality, and functional outcomes. Methods We searched PubMed, Embase, and Cochrane databases for randomized controlled trials (RCTs) comparing cemented with uncemented hemiarthroplasty in patients aged 50 years and older with femoral neck fractures. The primary outcome of interest was HRQoL as measured by the European Quality of Life 5‐Dimension Questionnaire (EQ‐5D) score. Secondary outcomes included mortality, surgical, general, and local complications. Results We included 20 RCTs with a total of 3680 patients with femoral neck fractures, of whom 1871 (50.5%) underwent cemented and 1809 (49.5%) uncemented hemiarthroplasty. The follow‐up ranged from 1 to 6 years. The early (after 3–4 months) EQ‐5D utility score (MD 0.07; 95% CI 0.03–0.12; p = 0.003; I 2 = 22%) and the 12‐month EQ‐5D utility score (MD 0.08; 95% CI 0.00–0.16; p = 0.04; I 2 = 67%) suggested an improved HRQoL in the cemented hemiarthroplasty group. The outcomes of 1‐year mortality, requirement for additional surgeries, surgery duration, risk of pulmonary embolism, pressure sores or ulcers, intraoperative fractures, and periprosthetic or postoperative fractures demonstrated significant differences between the two groups. Conclusions The use of cemented hemiarthroplasty in patients with femoral neck fractures presented better results when compared to uncemented hemiarthroplasty in terms of HRQoL during the first year after surgery and greater mortality reduction at 1 year follow‐up and reduced the need for further surgery. Therefore, the use of cemented hemiarthroplasty may be preferred for the treatment of femoral neck fractures in elderly patients.